Lead-acid battery
A cationic surfactant with long-chain aliphatic hydrocarbon groups in the negative electrode material addresses the trade-off in lead-acid batteries by reducing overcharge electricity and maintaining charge acceptance, enhancing battery life and performance in PSOC conditions.
Patent Information
- Application Number
- JP2020197591
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-27
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-11-27
AI Technical Summary
Lead-acid batteries used in partial state of charge (PSOC) conditions face a trade-off between reducing overcharge electricity and maintaining high charge acceptance due to the accumulation of lead sulfate, which is exacerbated by the use of organic additives that either inhibit charge acceptance or electrolyte loss.
Incorporating a cationic surfactant with hydrophobic and hydrophilic groups, particularly a long-chain aliphatic hydrocarbon group, into the negative electrode material at a concentration of 10 ppm or more, which enhances adsorption to lead surfaces while minimizing uneven distribution, thereby reducing overcharge electricity and maintaining charge acceptance.
The solution effectively reduces overcharge electricity while ensuring high charge acceptance by suppressing hydrogen generation and lead sulfate solubility, thus extending the battery's life and performance.
Smart Images

Figure 0007608799000004 
Figure 0007608799000001 
Figure 0007608799000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a lead-acid battery. [Background technology]
[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries include negative and positive plates, separators (or mats), and electrolytes. Additives are sometimes added to the components of lead-acid batteries to impart various functions.
[0003] Patent Document 1 discloses a flooded lead-acid battery having a configuration in which a negative electrode plate formed by packing a negative electrode active material in a negative electrode current collector and a positive electrode plate formed by packing a positive electrode active material in a positive electrode current collector are stacked with a separator interposed therebetween, the plate group being accommodated in a battery container together with an electrolyte, in which charging is performed intermittently and high-rate discharging to a load is performed in a partially charged state, in which at least a carbonaceous conductive material and an organic compound that suppresses coarsening of the negative electrode active material due to charging and discharging are added to the negative electrode active material, and the positive electrode plate has a unit plate pack volume [cm 3 ] Total surface area of positive electrode active material [m 2 ] to 3.5 to 15.6 [m 2 / cm 3 In addition, a compound selected from a cationic flocculant, a cationic surfactant, and phosphoric acid is added to the electrolyte.
[0004] Patent Document 2 proposes an electrolyte for a lead acid battery containing an ammonium compound represented by a specific formula (I).
[0005] Patent Document 3 proposes a rechargeable electrochemical cell that is subjected to multiple charge and discharge cycles, each charge cycle having a charge portion corresponding to a gassing charge where gas is generated in the cell and a charge portion lower than the gassing charge, the electrochemical cell having a positive electrode and a negative electrode, an aqueous electrolyte in ionic contact with the electrodes to support a current flow between the electrodes, and an inactivatable inhibiting means disposed in the electrolyte and a component thereof bound to the negative electrode to form a barrier inhibiting the gassing charge, the inactivatable inhibiting means being activated by a charge portion corresponding to the gassing charge such that when activated, the inactivatable inhibiting means inhibits the gassing charge and limits gas generation in the cell, and when inactivated, the inactivatable inhibiting means has substantially no effect of limiting the charge, and is inactivated by a charge portion lower than the gassing charge such that the inactivatable inhibiting means has substantially no effect during the discharge cycle. Patent Document 3 describes a quaternary ammonium such as alkyl dimethyl benzyl ammonium chloride as the inactivatable inhibiting means. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2013 / 058058 [Patent Document 2] JP 2008-152973 A [Patent Document 3] US Patent Application Publication No. 2002 / 0102467 Summary of the Invention [Problem to be solved by the invention]
[0007] Lead-acid batteries are sometimes used in a partially charged state (PSOC). For example, lead-acid batteries installed in idle stop-start (ISS) vehicles are used in PSOC. When lead-acid batteries are repeatedly charged and discharged in PSOC, lead sulfate easily accumulates and the life performance is easily reduced. In order to suppress the accumulation of lead sulfate, high charge acceptance is required. However, when the charge acceptance is high, the reduction reaction of hydrogen ions during overcharging also becomes prominent, so the overcharged amount of electricity increases and the decrease in electrolyte becomes significant. When the surface of the lead contained in the negative electrode material is covered with an organic additive, the reduction reaction of hydrogen ions during overcharging becomes difficult to occur, so the overcharged amount of electricity can be reduced. However, when the surface of the lead is covered with an organic additive, the lead sulfate generated during discharge becomes difficult to dissolve during charging, so the charge acceptance decreases. Therefore, it is difficult to suppress the decrease in charge acceptance while reducing the overcharged amount of electricity. [Means for solving the problem]
[0008] One aspect of the present invention is a lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate comprises a negative electrode material, The negative electrode material includes a cationic surfactant having one or more hydrophobic groups and hydrophilic groups; At least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms; The content of the cationic surfactant in the negative electrode material is 10 ppm or more by mass. Effect of the Invention
[0009] In a lead-acid battery, the amount of overcharged electricity can be reduced while ensuring a relatively high charge acceptance. [Brief description of the drawings]
[0010] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In general, in a lead-acid battery, the reaction during overcharging is greatly influenced by the reduction reaction of hydrogen ions at the interface between lead and the electrolyte. When an organic additive is contained in the negative electrode material of a lead-acid battery, the organic additive adheres to the surface of lead, which is an active material. When the surface of lead is covered with an organic additive, the reduction reaction of hydrogen ions is difficult to occur, so that the overcharged quantity of electricity tends to decrease. However, the organic additive also adheres to the surface of lead sulfate generated during discharge, making it difficult for lead sulfate to dissolve during charging, and thus the charge acceptance decreases. Therefore, there is a trade-off between suppressing the decrease in charge acceptance and reducing the overcharged quantity of electricity, and it has been difficult to achieve both in the past. Furthermore, when the organic additive is unevenly distributed in the pores of the lead, it is necessary to increase the content of the organic additive in the negative electrode material in order to ensure a sufficient effect of reducing the overcharged quantity of electricity. However, generally, increasing the content of the organic additive reduces the charge acceptance.
[0012] In lead-acid batteries, sulfuric acid aqueous solution is generally used as the electrolyte, so if an organic additive (oil, polymer, organic shrinkage inhibitor, etc.) is contained in the negative electrode material, it becomes difficult to balance the elution into the electrolyte and the adsorption to lead. For example, if an organic additive with low adsorption to lead is used, it becomes easy to elute into the electrolyte, making it difficult to reduce the amount of overcharge electricity. On the other hand, if an organic additive with high adsorption to lead is used, it becomes difficult to adhere thinly to the lead surface, and the organic additive tends to be unevenly distributed in the pores of the lead.
[0013] When organic additives are unevenly distributed within the pores of the lead, the steric hindrance of the unevenly distributed organic additives inhibits the movement of ions (such as lead ions and sulfate ions). This makes it easier for charge and discharge reactions to be inhibited. If the content of the organic additives is increased in order to ensure a sufficient effect of reducing the amount of overcharge electricity, the movement of ions within the pores is further inhibited, further inhibiting the charge and discharge reactions. If the charge and discharge reactions are inhibited, the charge acceptance and discharge performance will decrease.
[0014] In view of the above, a lead acid battery according to one aspect of the present invention includes at least one cell including an electrode plate group and an electrolyte. The electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate. The negative electrode plate includes a negative electrode material. The negative electrode material includes a cationic surfactant having one or more hydrophobic groups and hydrophilic groups. At least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms. The content of the cationic surfactant in the negative electrode material is 10 ppm or more by mass. In this specification, a cationic surfactant having one or more hydrophobic groups and hydrophilic groups, at least one of the hydrophobic groups being a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms, is sometimes referred to as a first surfactant.
[0015] In a lead-acid battery according to one aspect of the present invention, the negative electrode material contains 10 ppm or more of the first surfactant by mass. With this configuration, it is possible to reduce the amount of electricity in overcharge while ensuring a relatively high charge acceptance. By suppressing hydrogen generation during overcharge, the amount of electrolyte loss can be reduced, which is advantageous for extending the life of the lead-acid battery.
[0016] The lead-acid battery according to one aspect of the present invention can reduce the amount of overcharge electricity while ensuring a relatively high charge acceptance for the following reasons. First, the hydrophilic group of the first surfactant ensures high adsorption to lead. More specifically, in the negative electrode material, hydrogen sulfate ions having a negative charge are adsorbed to the surface of lead. The first surfactant has a cationic hydrophilic group, and therefore exhibits high adsorption to the surface of lead. On the other hand, the long-chain aliphatic hydrocarbon group having 8 or more carbon atoms prevents the first surfactant from excessively covering the surface of lead. Therefore, a wide area of the surface of lead is thinly and widely covered with the first surfactant. This increases the hydrogen overvoltage, making it difficult for a side reaction to occur in which hydrogen is generated during overcharge, and therefore the amount of overcharge electricity can be reduced. Even if the negative electrode material contains a very small amount of the first surfactant, the effect of reducing the amount of overcharge electricity can be obtained. Therefore, by including the first surfactant in the negative electrode material, the first surfactant can be present in the vicinity of lead, and this is believed to enable the first surfactant to exhibit a high adsorption effect on lead. In addition, since the negative electrode material contains the first surfactant, the first surfactant is likely to adhere to the surface of lead sulfate generated during discharge, and therefore the solubility of lead sulfate during charging tends to decrease. However, since the thickness of the coating of the first surfactant covering the surface of lead and lead sulfate is thin, the degree to which the coating of the first surfactant inhibits the dissolution of lead sulfate and the transfer of electrons when lead ions are reduced to lead during charging is reduced. In addition, since the coating of the first surfactant is thin and uneven distribution is suppressed, the steric hindrance caused by the coating of the first surfactant is reduced, and the inhibition of the movement of lead ions in the pores of the negative electrode material is reduced. Therefore, a high diffusion rate of lead ions is maintained. As a result, even when the negative electrode material contains the first surfactant, which is an organic additive, it is possible to reduce the inhibition of the charge / discharge reaction, and it is believed that the decrease in charge acceptance is suppressed.
[0017] The effect of reducing the overcharge quantity of electricity is exhibited by covering the surface of lead in the negative electrode material with the first surfactant. Therefore, it is important that the first surfactant is present in the vicinity of lead in the negative electrode material, and this allows the effect of the first surfactant to be effectively exhibited. Therefore, regardless of whether the first surfactant is contained in components of the lead-acid battery other than the negative electrode material, it is important that the negative electrode material contains the first surfactant in the specific content as described above.
[0018] At least one of the hydrophobic groups of the first surfactant is preferably a long-chain aliphatic hydrocarbon group having a carbon number of 16 or more. In this case, the adsorptivity to the lead surface is enhanced, thereby making it possible to further reduce the amount of overcharge electricity.
[0019] Cationic surfactants are generally classified into amine salt type, quaternary ammonium salt type, etc. The first surfactant preferably contains a quaternary ammonium salt (in other words, a cationic surfactant of quaternary ammonium salt type). When a quaternary ammonium salt is used, it exhibits higher adsorption to the lead surface than an amine salt due to its high cationicity, and therefore the amount of electricity in overcharge can be further reduced.
[0020] The number of carbon atoms in the long-chain aliphatic hydrocarbon group in the first surfactant is preferably 26 or less. In this case, it is possible to ensure higher adsorption of the first surfactant to the lead surface in the negative electrode material. In addition, the negative electrode material may contain a carbonaceous material, and when the carbon water in the long-chain aliphatic hydrocarbon group is 26 or less, the adsorption of the first surfactant to the carbonaceous material is reduced, and adsorption to the lead surface is more likely to occur. Therefore, the amount of electricity in overcharge can be further reduced.
[0021] In this way, the first surfactant can thinly cover the lead surface while having high adsorption to lead due to the action of the hydrophilic group and hydrophobic group of the first surfactant. Therefore, even if the content of the first surfactant in the negative electrode material is small, the overcharged electric charge can be reduced. In addition, even if the content is small, a sufficient effect of reducing the overcharged electric charge can be ensured, so that the decrease in charge acceptance can be suppressed. From the viewpoint of easily ensuring a higher charge acceptance, the content of the first surfactant in the negative electrode material is preferably 600 ppm or less by mass. From the viewpoint of ensuring a higher effect of reducing the overcharged electric charge, the content of the first surfactant in the negative electrode material is preferably 50 ppm or more.
[0022] In this specification, the content of the first surfactant in the negative electrode material is determined for a negative electrode plate taken out from a fully charged lead-acid battery.
[0023] In the lead-acid battery, the origin of the first surfactant contained in the negative electrode material is not particularly limited as long as the first surfactant can be contained in a predetermined content in the negative electrode material. The first surfactant may be contained in any of the components of the lead-acid battery (e.g., the negative electrode plate, the positive electrode plate, the electrolyte, and the separator) when the lead-acid battery is produced. The first surfactant may be contained in one component, or in two or more components (e.g., the negative electrode plate and the electrolyte).
[0024] The negative electrode material preferably contains a condensate of a bisarene compound. The condensate of a bisarene compound corresponds to an organic shrinkage inhibitor. When the negative electrode material contains an organic shrinkage inhibitor, high discharge performance is easily obtained. The condensate of a bisarene compound is generally classified as a synthetic organic shrinkage inhibitor. When the negative electrode material contains a condensate of a bisarene compound, the specific surface area of the negative electrode material increases, so that the overcharged amount of electricity tends to increase. However, even in such a case, the overcharged amount of electricity can be kept low by the action of the first surfactant. In addition, by using the condensate of a bisarene compound, the uneven distribution of the organic shrinkage inhibitor on the surface of the lead is suppressed compared to the case where a lignin compound is used, so that a higher charge acceptance is easily obtained. In addition, when the condensate of a bisarene compound is used, even when the lead-acid battery is charged and discharged at high temperatures, the deterioration of the negative plate is suppressed, and high discharge performance can be ensured.
[0025] The lead acid battery may be either a valve regulated (sealed) lead acid battery (VRLA type lead acid battery) or a flooded (vented) lead acid battery.
[0026] (Terminology explanation) (electrode material) The negative electrode material and the positive electrode material of the positive electrode plate are usually held by a current collector. The electrode material is the portion of the electrode plate excluding the current collector. A member such as a mat or pasting paper may be attached to the electrode plate. Such a member (also called an attachment member) is included in the electrode plate because it is used integrally with the electrode plate. When the electrode plate includes an attachment member (such as a mat or pasting paper), the electrode material is the portion of the electrode plate excluding the current collector and the attachment member.
[0027] Among the positive electrode plates, the clad type positive electrode plate includes a plurality of porous tubes, a metal core inserted into each tube, a current collector connecting the plurality of metal cores, a positive electrode material filled into the tube into which the metal core is inserted, and a connecting seat connecting the plurality of tubes. In the clad type positive electrode plate, the positive electrode material is the portion of the plate excluding the tube, the metal core, the current collector, and the connecting seat. In the clad type positive electrode plate, the metal core and the current collector are sometimes collectively referred to as the positive electrode current collector.
[0028] (Hydrophobic and Hydrophilic Groups of the First Surfactant) The first surfactant is a cationic surfactant. Therefore, the hydrophilic group of the first surfactant is a hydrophilic group that can be dissociated into a cation in an aqueous solution of the first surfactant. The hydrophobic group of the first surfactant is a functional group that is more hydrophobic than the hydrophilic group. At least one of the hydrophobic groups of the first surfactant may be a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms.
[0029] (Organic shrink-proofing agent) The organic shrinkage inhibitor is an organic compound that inhibits the shrinkage of lead, the negative electrode active material, when a lead-acid battery is repeatedly charged and discharged. Organic shrinkage inhibitors often contain sulfur element.
[0030] (Sulfur content in organic shrinkage inhibitors) The content of sulfur element in an organic shrink-preventer being X μmol / g means that the content of sulfur element contained in 1 g of the organic shrink-preventer is X μmol.
[0031] (Condensation product of bisarene compound) The condensation product of a bisarene compound is a condensation product containing a unit of a bisarene compound. The unit of a bisarene compound refers to a unit derived from a bisarene compound incorporated in the condensation product. A bisarene compound is a compound in which two parts each having an aromatic ring are linked via a single bond or a linking group.
[0032] (Weight average molecular weight) In this specification, the weight average molecular weight (Mw) is determined by GPC. The standard substance used in determining Mw is sodium polystyrene sulfonate.
[0033] (fully charged) The fully charged state of a flooded lead-acid battery is defined by JIS D 5301:2019. More specifically, the fully charged state is defined as a state in which the lead-acid battery is charged at a current (A) that is 0.2 times the value (unit: Ah) listed as the rated capacity until the terminal voltage (V) during charging measured every 15 minutes or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times in a water tank at 25°C ± 2°C. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which constant-current constant-voltage charging of 2.23 V / cell is performed in an air tank at 25°C ± 2°C at a current (A) that is 0.2 times the value (unit: Ah) listed as the rated capacity, and charging is terminated when the charging current during constant-voltage charging becomes 0.005 times the value (unit: Ah) listed as the rated capacity.
[0034] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically prepared and is fully charged. A lead-acid battery may be fully charged immediately after chemical preparation, or after a certain amount of time has passed since chemical preparation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after chemical preparation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.
[0035] (Top and bottom directions of lead-acid batteries or components of lead-acid batteries) In this specification, the up-down direction of a lead-acid battery or components of the lead-acid battery (such as plates, a battery case, and a separator) refers to the up-down direction in the vertical direction of the lead-acid battery when the lead-acid battery is in use. Each of the positive and negative plates has a lug for connecting to an external terminal. In some cases, such as a horizontal valve-regulated lead-acid battery, the lug is provided on the side of the plate so as to protrude laterally, but in most lead-acid batteries, the lug is usually provided on the top of the plate so as to protrude upward.
[0036] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.
[0037] [Lead acid battery] (Negative plate) The negative electrode plate usually includes a negative electrode current collector in addition to a negative electrode material.
[0038] (Negative electrode current collector) The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.
[0039] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.
[0040] (Negative electrode material) The negative electrode material includes a first surfactant. The negative electrode material further includes a negative electrode active material (specifically, lead or lead sulfate) that exhibits capacity through an oxidation-reduction reaction. The negative electrode material may include at least one selected from the group consisting of an organic shrinkage inhibitor, a carbonaceous material, and other additives. Examples of the additives include barium sulfate, fibers (such as resin fibers), and a surfactant other than the first surfactant (also referred to as a second surfactant). However, the additives are not limited to these. The negative electrode active material in a charged state is sponge lead, but an unformed negative plate is usually made using lead powder.
[0041] (First Surfactant) The first surfactant, which is a cationic surfactant, is classified into an amine salt type and a quaternary ammonium salt type according to the type of hydrophilic group. In the first surfactant, the amine salt portion or the quaternary ammonium salt portion corresponds to the hydrophilic group. In the negative electrode material, the hydrophilic group may exist in the form of a salt or in the form of a cation. The type of anion forming the salt is not particularly limited, and examples thereof include halide ions and anions derived from inorganic acids. Examples of halide ions include fluoride ions, chloride ions, bromide ions, and iodide ions. Examples of inorganic acids corresponding to anions derived from inorganic acids include hydrohalic acids (such as hydrochloric acid and hydrobromic acid) or oxo acids (such as sulfuric acid and phosphoric acid).
[0042] The first surfactant usually has one hydrophilic group in one molecule, but it is not intended to exclude the case where the first surfactant has a plurality of hydrophilic groups in one molecule.
[0043] The first surfactant has one or more hydrophobic groups in one molecule. The number of hydrophobic groups in the first surfactant may be one or more, and may be two or more, or three or more. The amine salt type first surfactant may usually have one or more and three or less hydrophobic groups per nitrogen atom of the amine salt. The quaternary ammonium salt type first surfactant may usually have four hydrophobic groups per nitrogen atom of the ammonium salt.
[0044] At least one of the hydrophobic groups possessed by the first surfactant is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms. The long-chain aliphatic hydrocarbon group having 8 or more carbon atoms possessed by the first surfactant may be referred to as the first hydrophobic group. The first surfactant may have one or more hydrophobic groups (also referred to as the second hydrophobic group) other than the first hydrophobic group.
[0045] The first surfactant may have one first hydrophobic group in one molecule, or may have two or more first hydrophobic groups. When the first surfactant has two or more first hydrophobic groups in one molecule, the types of at least two first hydrophobic groups may be the same, or all the first hydrophobic groups may be different. The upper limit of the number of first hydrophobic groups in the first surfactant is not particularly limited. In the amine salt type, the number of first hydrophobic groups is, for example, 3 or less, and may be 2 or less. In the quaternary ammonium salt type, the number of first hydrophobic groups is, for example, 4 or less, and may be 3 or less or 2 or less.
[0046] The number of first hydrophobic groups contained in one molecule of the first surfactant is, in the case of an amine salt type, for example, 1 to 3, and may be 1 to 2, or may be 2 to 3. The number of first hydrophobic groups contained in one molecule of the first surfactant is, in the case of a quaternary ammonium salt type, for example, 1 to 4, and may be 1 to 3 or 1 to 2, or may be 2 to 4 or 2 to 3. When the first surfactant has two or more first hydrophobic groups, the effect of reducing the overcharge electricity can be enhanced.
[0047] The first surfactant may have one second hydrophobic group, or may have two or more. When the first surfactant has two or more second hydrophobic groups, the types of at least two second hydrophobic groups may be the same, or all the second hydrophobic groups may be different. The upper limit of the number of second hydrophobic groups is not particularly limited, and may be, for example, 2 or less in the amine salt type, and may be, for example, 3 or less or 2 or less in the quaternary ammonium salt type. In the first surfactant, the total number of the first hydrophobic groups and the second hydrophobic groups in one molecule is set to not exceed 3 per nitrogen atom in the amine salt type, and not exceed 4 per nitrogen atom in the quaternary ammonium salt type.
[0048] The first hydrophobic group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group. The first hydrophobic group may be either linear or branched. Examples of the first hydrophobic group include an alkyl group and an alkenyl group. The first hydrophobic group may be a dienyl group having two carbon-carbon double bonds, a trienyl group having three carbon-carbon double bonds, or the like. From the viewpoint of making it easier to reduce the thickness of the coating of the first surfactant formed on the lead surface, the first hydrophobic group is preferably an alkyl group or an alkenyl group.
[0049] The number of carbon atoms in the first hydrophobic group may be 8 or more. From the viewpoint of easily reducing the thickness of the coating of the first surfactant formed on the lead surface, the number of carbon atoms in the first hydrophobic group is preferably 10 or more, and may be 14 or more, 16 or more, or may be 18 or more. The number of carbon atoms in the first hydrophobic group is, for example, 30 or less. From the viewpoint of easily ensuring high adsorptivity of the first surfactant to the lead surface by a balance with the hydrophilic group, the number of carbon atoms in the first hydrophobic group is preferably 26 or less, and more preferably 24 or less, or 22 or less.
[0050] The number of carbon atoms in the first hydrophobic group may be 8 to 30 (or 26 or less), 10 to 30 (or 26 or less), 14 to 30 (or 26 or less), 16 to 30 (or 26 or less), 18 to 30 (or 26 or less), 8 to 24 (or 22 or less), 10 to 24 (or 22 or less), 14 to 24 (or 22 or less), 16 to 24 (or 22 or less), or 18 to 24 (or 22 or less).
[0051] Specific examples of alkyl groups include 2-ethylhexyl, n-octyl, n-nonyl, n-decyl, i-decyl, lauryl (dodecyl), myristyl, cetyl, stearyl, and behenyl. Specific examples of alkenyl groups include palmitoleyl and oleyl. Alkenyl groups include, for example, C 2-30 Alkenyl group or C 2-26 may be an alkenyl group, C 2-24 may be an alkenyl group, C 2-22may be an alkenyl group, C 10-22 It may be an alkenyl group.
[0052] Examples of the second hydrophobic group include a hydrocarbon group. The hydrocarbon group also includes a hydrocarbon group having a substituent (e.g., a hydroxy group, an alkoxy group, and / or a carboxy group). The hydrocarbon group may be any of aliphatic, alicyclic, and aromatic. The aliphatic hydrocarbon group may have at least one selected from the group consisting of an aromatic hydrocarbon group (e.g., a phenyl group, a tolyl group, a naphthyl group) and an alicyclic hydrocarbon group (e.g., a cyclopentyl group, a cyclohexyl group) as a substituent. Examples of the aliphatic hydrocarbon group having such a substituent include a benzyl group, a phenethyl group, and a cyclohexylmethyl group. The number of carbon atoms of the aromatic hydrocarbon group and the alicyclic hydrocarbon group as the substituent is, for example, 5 or more and 20 or less, and may be 6 or more and 12 or less. The aromatic hydrocarbon group and the alicyclic hydrocarbon group may have an aliphatic hydrocarbon group (e.g., an alkyl group, an alkenyl group, an alkynyl group) as a substituent. The aliphatic hydrocarbon group as a substituent may have 1 to 30 carbon atoms, 1 to 20 or 1 to 10 carbon atoms, or 1 to 6 or 1 to 4 carbon atoms, for example.
[0053] Examples of the aromatic hydrocarbon group include aromatic hydrocarbon groups having 24 or less carbon atoms (e.g., 6 to 24). The number of carbon atoms in the aromatic hydrocarbon group may be 20 or less (e.g., 6 to 20), 14 or less (e.g., 6 to 14), or 12 or less (e.g., 6 to 12). Examples of the aromatic hydrocarbon group include aryl groups and bisaryl groups. Examples of the aryl group include phenyl groups and naphthyl groups. Examples of the bisaryl group include monovalent groups corresponding to bisarenes. Examples of the bisarenes include biphenyl, bisarylalkanes (e.g., bisC 6-10 Aryl C 1-4 Alkanes (such as 2,2-bisphenylpropane) are examples.
[0054] Examples of the alicyclic hydrocarbon group include alicyclic hydrocarbon groups having 16 or less carbon atoms. The alicyclic hydrocarbon group may be a cross-linked cyclic hydrocarbon group. The number of carbon atoms in the alicyclic hydrocarbon group may be 10 or less or 8 or less. The number of carbon atoms in the alicyclic hydrocarbon group may be, for example, 5 or more, or 6 or more.
[0055] The alicyclic hydrocarbon group may have 5 (or 6) or more and 16 (or less), 5 (or 6) or more and 10 (or less), or 5 (or 6) or more and 8 (or less) carbon atoms.
[0056] Examples of alicyclic hydrocarbon groups include cycloalkyl groups (cyclopentyl, cyclohexyl, cyclooctyl, etc.) and cycloalkenyl groups (cyclohexenyl, cyclooctenyl, etc.). Alicyclic hydrocarbon groups also include hydrogenated products of the above aromatic hydrocarbon groups.
[0057] From the viewpoint of facilitating thin adhesion of the first surfactant to the lead surface, among the hydrocarbon groups, an aliphatic hydrocarbon group is preferred. Examples of the aliphatic hydrocarbon group include an alkyl group, an alkenyl group, an alkynyl group, and a dienyl group. The aliphatic hydrocarbon group may be either linear or branched.
[0058] The carbon number of the aliphatic hydrocarbon group is less than 8, and may be 7 or less or 6 or less. The lower limit of the carbon number is 1 or more for an alkyl group, 2 or more for an alkenyl group and an alkynyl group, and 3 or more for a dienyl group, depending on the type of the aliphatic hydrocarbon group. As the second hydrophobic group, an alkyl group and an alkenyl group (among which, an alkyl group) are preferable. The carbon number of the alkyl group is more preferably 4 or less, and may be 3 or less or 2 or less.
[0059] Specific examples of alkyl groups include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, s-butyl, t-butyl, n-pentyl, neopentyl, i-pentyl, s-pentyl, 3-pentyl, t-pentyl, and n-hexyl.Specific examples of alkenyl groups include vinyl, 1-propenyl, and allyl.
[0060] From the viewpoint of easily obtaining high adsorption to lead due to high hydrophilicity, the first surfactant preferably contains at least a quaternary ammonium salt type first surfactant. The first surfactant may contain an amine salt type first surfactant in addition to the quaternary ammonium salt type first surfactant.
[0061] Examples of the first surfactant of the quaternary ammonium salt type include tetraalkylammonium salts and alkylbenzalkonium chlorides. Examples of the tetraalkylammonium salts include first surfactants having one first hydrophobic group (such as octyltrimethylammonium chloride, stearyltrimethylammonium chloride, cetyltrimethylammonium chloride, and behenyltrimethylammonium chloride), and first surfactants having two first hydrophobic groups (such as distearyldimethylammonium chloride). Examples of the alkylbenzalkonium chloride include stearylbenzyldimethylammonium chloride, stearyldimethylbenzylammonium chloride, and stearylbenzalkonium chloride. Examples of the first surfactant of the amine salt type include n-octylamine hydrochloride and dodecylamine hydrochloride. These are merely examples, and the first surfactant is not limited to these specific examples.
[0062] The negative electrode material may contain one type of first surfactant, or may contain two or more types of first surfactant.
[0063] The content of the first surfactant in the negative electrode material may be, for example, 10 ppm or more by mass. From the viewpoint of further enhancing the effect of reducing the overcharge electricity amount, the content of the first surfactant in the negative electrode material is preferably 50 ppm or more by mass, more preferably 100 ppm or more, more preferably 150 ppm or more or 250 ppm or more, and may be 300 ppm or more by mass. The content of the first surfactant in the negative electrode material may be, for example, 1000 ppm or less, or 700 ppm or less by mass. From the viewpoint of easily ensuring higher charge acceptance, the content of the first surfactant in the negative electrode material is preferably 600 ppm or less or 500 ppm or less by mass, more preferably 400 ppm or less or 300 ppm or less by mass.
[0064] The content of the first surfactant in the negative electrode material is, by mass, 10 ppm or more and 1000 ppm or less (or 700 ppm or less), 50 ppm or more and 1000 ppm or less (or 700 ppm or less), 100 ppm or more and 1000 ppm or less (or 700 ppm or less), 150 ppm or more and 1000 ppm or less (or 700 ppm or less), 250 ppm or more and 1000 ppm or less (or 700 ppm or less), 300 ppm or more and 1000 ppm or less (or 700 ppm or less), 10 ppm or more and 600 ppm or less (or 500 ppm or less), 50 ppm or more and 600 ppm or less (or 500 ppm or less), 100 ppm or more and 600 ppm or less m or less (or 500 ppm or less), 150 ppm or more and 600 ppm or less (or 500 ppm or less), 250 ppm or more and 600 ppm or less (or 500 ppm or less), 300 ppm or more and 600 ppm or less (or 500 ppm or less), 10 ppm or more and 400 ppm or less (or 300 ppm or less), 50 ppm or more and 400 ppm or less (or 300 ppm or less), 100 ppm or more and 400 ppm or less (or 300 ppm or less), 150 ppm or more and 400 ppm or less (or 300 ppm or less), 250 ppm or more and 400 ppm or less (or 300 ppm or less), or 300 ppm or more and 400 ppm or less.
[0065] (Second Surfactant) The negative electrode material may contain a second surfactant other than the first surfactant. Examples of the second surfactant include a cationic surfactant other than the first surfactant, a nonionic surfactant, an anionic surfactant, and an amphoteric surfactant. The negative electrode material may contain one type of the second surfactant, or two or more types of the second surfactant.
[0066] The ratio of the first surfactant to the total surfactants contained in the negative electrode material is preferably as high as possible, and is preferably, for example, 70 mass% or more of the total surfactants, and may be 80 mass% or more or 90 mass% or more. The ratio of the first surfactant to the total surfactants is 100 mass% or less. The negative electrode material may contain only the first surfactant as a surfactant.
[0067] (Organic shrink-proofing agent) Organic shrink-proofing agents are generally classified into lignin compounds and synthetic organic shrink-proofing agents. Synthetic organic shrink-proofing agents can also be said to be organic shrink-proofing agents other than lignin compounds. Examples of organic shrink-proofing agents contained in the negative electrode material include lignin compounds and synthetic organic shrink-proofing agents. The negative electrode material may contain one type of organic shrink-proofing agent or two or more types of organic shrink-proofing agents.
[0068] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivatives include lignin sulfonic acid or salts thereof (alkali metal salts (sodium salts, etc.)).
[0069] The synthetic organic shrink-proofing agent is an organic polymer containing elemental sulfur, and generally contains multiple aromatic rings in the molecule and elemental sulfur as a sulfur-containing group. Among the sulfur-containing groups, sulfonic acid groups or sulfonyl groups, which are stable, are preferred. The sulfonic acid groups may exist in the acid form or in the salt form such as Na salt.
[0070] At least a lignin compound may be used as the organic shrinkage inhibitor. Lignin compounds tend to have low charge acceptance compared to synthetic organic shrinkage inhibitors. However, by including a first surfactant in the negative electrode material, high charge acceptance can be ensured even when a lignin compound is used as the organic shrinkage inhibitor.
[0071] As the organic shrink-proofing agent, it is also preferable to use a condensation product containing at least an aromatic compound unit. For example, such a condensation product may be a condensation product of an aromatic compound with an aldehyde compound (at least one selected from the group consisting of aldehydes (e.g., formaldehyde) and condensates thereof). The organic shrink-proofing agent may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product.
[0072] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When aromatic compounds have multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) and the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.). Examples of aromatic compounds include compounds having the above aromatic rings and at least one selected from the group consisting of hydroxyl groups and amino groups. The hydroxyl group or amino group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a hydroxyl group or amino group. The hydroxyl group also includes salts of the hydroxyl group (-OMe). The amino group also includes salts of the amino group (specifically, salts with anions). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.).
[0073] As the aromatic compound, a bisarene compound [bisphenol compound, hydroxybiphenyl compound, bisarene compound having an amino group (bisarylalkane compound having an amino group, bisarylsulfone compound having an amino group, biphenyl compound having an amino group, etc.), hydroxyarene compound (hydroxynaphthalene compound, phenol compound, etc.), aminoarene compound (aminonaphthalene compound, aniline compound (aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc.)), etc.] are preferable. The aromatic compound may further have a substituent. The organic shrinkage inhibitor may contain one or more of the residues of these compounds. As the bisphenol compound, bisphenol A, bisphenol S, bisphenol F, etc. are preferable. When the negative electrode material contains a condensate of a bisarene compound (such as a condensate of an aldehyde compound), it is possible to ensure higher charge acceptance while suppressing the overcharge electricity amount to a low level.
[0074] The condensate preferably contains at least a unit of an aromatic compound having a sulfur-containing group. In particular, the use of a condensate containing at least a unit of a bisphenol compound having a sulfur-containing group is advantageous in terms of ensuring higher charge acceptance. From the viewpoint of increasing the effect of reducing the amount of overcharge electricity, it is also preferable to use a condensate of an aldehyde compound with a naphthalene compound having a sulfur-containing group and at least one selected from the group consisting of a hydroxyl group and an amino group.
[0075] The sulfur-containing group may be directly bonded to an aromatic ring contained in the compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group. The sulfur-containing group is not particularly limited, and examples thereof include a sulfonyl group, a sulfonic acid group, and salts thereof.
[0076] Also, as the organic shrink-proofing agent, for example, at least one condensate containing at least one selected from the group consisting of the above-mentioned bisarene compound units and monocyclic aromatic compound units (hydroxyarene compounds and / or aminoarene compounds, etc.) may be used. The organic shrink-proofing agent may at least contain a condensate containing a bisarene compound unit and a monocyclic aromatic compound unit (particularly, a hydroxyarene compound). Such a condensate may be a condensate of a bisarene compound and a monocyclic aromatic compound with an aldehyde compound. As the hydroxyarene compound, a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) is preferable. As the aminoarene compound, aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc. are preferable. As the monocyclic aromatic compound, a hydroxyarene compound is preferable.
[0077] The negative electrode material may contain, for example, an organic shrink-proofing agent (first organic shrink-proofing agent) having a sulfur element content of 2000 μmol / g or more among the above organic shrink-proofing agents. Examples of the first organic shrink-proofing agent include the above synthetic organic shrink-proofing agents (such as the above condensates).
[0078] The sulfur element content of the first organic shrinkage inhibitor may be 2000 μmol / g or more, and is preferably 3000 μmol / g or more. The upper limit of the sulfur element content of the first organic shrinkage inhibitor is not particularly limited. From the viewpoint of further enhancing the effect of reducing the amount of overcharge electricity, the sulfur element content of the first organic shrinkage inhibitor is preferably 9000 μmol / g or less, and more preferably 8000 μmol / g or less.
[0079] The sulfur element content of the first organic shrink inhibitor may be, for example, 2000 μmol / g or more (or 3000 μmol / g or more) and 9000 μmol / g or less, or 2000 μmol / g or more (or 3000 μmol / g or more) and 8000 μmol / g or less.
[0080] The first organic shrinkage inhibitor includes a condensate including a unit of an aromatic compound having a sulfur-containing group, and the condensate may include at least a unit of a bisarene compound (such as a bisphenol compound) as the unit of the aromatic compound.
[0081] The weight average molecular weight (Mw) of the first organic shrink-proofing agent is preferably equal to or greater than 7000. The Mw of the first organic shrink-proofing agent is, for example, equal to or less than 100,000, and may be equal to or less than 20,000.
[0082] The negative electrode material may contain, for example, an organic shrink-proofing agent (second organic shrink-proofing agent) having a sulfur element content of less than 2000 μmol / g. The second organic shrink-proofing agent may be, among the above organic shrink-proofing agents, a lignin compound, a synthetic organic shrink-proofing agent (particularly, a lignin compound), or the like. The sulfur element content of the second organic shrink-proofing agent is preferably 1000 μmol / g or less, and may be 800 μmol / g or less. The lower limit of the sulfur element content in the second organic shrink-proofing agent is not particularly limited, and is, for example, 400 μmol / g or more.
[0083] The Mw of the second organic shrink-proofing agent is, for example, less than 7000. The Mw of the second organic shrink-proofing agent is, for example, 3000 or more.
[0084] The negative electrode material may contain a second organic shrink-proofing agent in addition to the first organic shrink-proofing agent. When the first organic shrink-proofing agent and the second organic shrink-proofing agent are used in combination, the mass ratio thereof can be selected arbitrarily.
[0085] The content of the organic shrinkage inhibitor contained in the negative electrode material is, for example, 0.005% by mass or more, and may be 0.01% by mass or more. When the content of the organic shrinkage inhibitor is in such a range, a high discharge capacity can be ensured. The content of the organic shrinkage inhibitor is, for example, 1.0% by mass or less, and may be 0.5% by mass or less. From the viewpoint of further enhancing the effect of suppressing the decrease in charge acceptance, the content of the organic shrinkage inhibitor is preferably 0.3% by mass or less, and more preferably 0.25% by mass or less.
[0086] The content of the organic shrinkage preventer in the negative electrode material may be 0.005% by mass or more (or 0.01% by mass or more) and 1.0% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) and 0.5% by mass or less, 0.005% by mass or more (or 0.01% by mass or more) and 0.3% by mass or less, or 0.005% by mass or more (or 0.01% by mass or more) and 0.25% by mass or less.
[0087] (carbonaceous material) Examples of the carbonaceous material contained in the negative electrode material include carbon black, graphite, hard carbon, and soft carbon. Examples of carbon black include acetylene black, furnace black, and lamp black. Furnace black also includes Ketjen Black (trade name).
[0088] In this specification, among the carbonaceous materials, -1 More than 1350cm -1 Peaks appearing in the following range (D band) and 1550 cm -1 More than 1600cm -1 Intensity ratio I to the peak (G band) appearing in the following range D / I G A carbonaceous material having a σ of 0 or more and 0.9 or less is called graphite. Graphite may be either artificial graphite or natural graphite.
[0089] The negative electrode material may contain one type of carbonaceous material or may contain two or more types of carbonaceous materials.
[0090] Since the first surfactant also covers the surface of the carbonaceous material, the coating amount for lead and lead sulfate is also affected by the specific surface area and amount of the carbonaceous material.
[0091] The specific surface area of the carbonaceous material is, for example, 0.5 (m 2 ·g -1 ) or more, and 1(m 2 ·g -1 ) or more than 20(m 2 ·g -1) or more. When the specific surface area is in this range, it is easy to prevent the content of the first surfactant from becoming excessively large, and it is easy to ensure high charge acceptance. The specific surface area of the carbonaceous material may be 300 (m 2 ·g -1 ) or more than 400(m 2 ·g -1 ) or more. When the specific surface area is in this range, the amount of electricity for overcharging tends to be large, but even in such a case, the amount of electricity for overcharging can be reduced by combining with the first surfactant. The specific surface area of the carbonaceous material may be, for example, 1500 (m 2 ·g -1 ) or less, and 1000(m 2 ·g -1 ) or less, and 800 (m 2 ·g -1 ) or less, and 200 (m 2 ·g -1 ) or less than 150(m 2 ·g -1 When the specific surface area is in this range, the effect of reducing the overcharge electricity quantity can be further increased.
[0092] The specific surface area of carbonaceous materials is 0.5 (m 2 ·g -1 ) or more 1500(m 2 ·g -1 ) or less (or 1000(m 2 ·g -1 ) or less), 1(m 2 ·g -1 ) or more 1500(m 2 ·g -1 ) or less (or 1000(m 2 ·g -1 ) or less), 20(m 2 ·g -1 ) or more 1500(m 2 ·g -1 ) or less (or 1000(m 2 ·g -1 ) or less), 300(m 2 ·g -1 ) or more 1500(m 2 ·g -1 ) or less (or 1000(m2 ·g -1 ) or less), 400(m 2 ·g -1 ) or more 1500(m 2 ·g -1 ) or less (or 1000(m 2 ·g -1 ) or less), 300(m 2 ·g -1 ) or more (or 400 (m 2 ·g -1 ) or more) 800(m 2 ·g -1 ) or less, 0.5(m 2 ·g -1 ) or more 800(m 2 ·g -1 ) or less (or 200 (m 2 ·g -1 ) or less), 1(m 2 ·g -1 ) or more 800(m 2 ·g -1 ) or less (or 200 (m 2 ·g -1 ) or less), 20(m 2 ·g -1 ) or more 800(m 2 ·g -1 ) or less (or 200 (m 2 ·g -1 ) or less), 0.5(m 2 ·g -1 ) or more 150(m 2 ·g -1 ) or less, 1(m 2 ·g -1 ) or more 150(m 2 ·g -1 ) or less, or 20(m 2 ·g -1 ) or more 150(m 2 ·g -1 ) or less.
[0093] The specific surface area of the carbonaceous material is a BET specific surface area determined by a gas adsorption method using nitrogen gas.
[0094] The content of the carbonaceous material in the negative electrode material is, for example, 0.05 mass% or more, and may be 0.10 mass% or more.The content of the carbonaceous material is, for example, 5 mass% or less, and may be 3 mass% or less.
[0095] The content of the carbonaceous material in the negative electrode material may be 0.05% by mass to 5% by mass, 0.05% by mass to 3% by mass, 0.10% by mass to 5% by mass, or 0.10% by mass to 3% by mass.
[0096] (Barium Sulfate) The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of barium sulfate in the negative electrode material is, for example, 3% by mass or less, and may be 2% by mass or less.
[0097] The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.
[0098] (Analysis of negative electrode materials or components) The method of analyzing the negative electrode material or its constituents is described below. Prior to measurement or analysis, a fully charged lead-acid battery is disassembled to obtain a negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. If the negative plate contains an adhesive material after drying, the adhesive material is removed by peeling. Next, the negative electrode material is separated from the negative plate to obtain a sample (hereinafter referred to as sample A). Sample A is crushed as necessary and subjected to analysis.
[0099] (1) Analysis of surfactants (1-1) Qualitative analysis of the first surfactant Crushed sample A is used. Approximately 1 g of sample A is collected and accurately weighed, and 5 mL of chloroform is added to prepare a mixture. The mixture is stirred at 20±5°C for 5.5 hours while applying ultrasonic waves to extract the first surfactant. The filtrate is then collected by filtration, and the filtered solid matter and the container are washed with chloroform to collect the washing liquid. The filtrate and washing liquid are mixed and concentrated using nitrogen gas.
[0100] The first surfactant is identified by obtaining information from at least one of infrared spectroscopy, ultraviolet-visible absorption spectroscopy, NMR spectroscopy, liquid chromatography / mass spectrometry (LC / MS), and pyrolysis gas chromatography / mass spectrometry (GC / MS) for the resulting concentrate. Note that, since the counter anion of the cationic surfactant may be ion-exchanged in sulfuric acid, the structure other than the counter anion is identified.
[0101] (1-2) Quantitative analysis of the first surfactant The concentrate obtained in the same manner as in (1-1) above is diluted with chloroform until the volume of the solution becomes 10 mL. In this way, a sample for analysis (sample B) is prepared.
[0102] The content of the first surfactant in the negative electrode material is quantified by LC / MS analysis using the SRM (selected reaction monitoring) method using sample B. More specifically, the LC / MS spectrum of sample B is measured, and the concentration of the first surfactant in sample B is determined by a calibration curve method from the peak intensity of a specific peak characteristic of the first surfactant. Then, the content of the first surfactant in the negative electrode material is determined from the determined concentration and the mass of sample A collected during the preparation of sample B. The calibration curve showing the relationship between the peak intensity of the specific peak and the concentration of the first surfactant in the analytical material is created in advance by separately preparing the first surfactant identified by qualitative analysis and using this first surfactant. For example, when the first surfactant is behenyltrimethylammonium chloride, a characteristic peak is detected at m / z=368.5 in the LC / MS spectrum. The LC / MS analysis is performed under the following conditions.
[0103] LC / MS equipment: LC section (Agilent Technologies, 1200 Series), MS section (Agilent Technologies, 6140) Column: Imtakt Unison UK-C18 UP (inner diameter 2 mm, length 10 cm) Column temperature: 50℃±1℃ Mobile phase: A mixture of the first and second solutions is used, and the mixing ratio of the first and second solutions is gradually changed from 20:80 (volume ratio) to 0:100 (volume ratio) over 3 minutes, and only the second solution is used from 3 minutes to 10 minutes later. First solution=aqueous solution containing 10 mmol / L ammonium formate and 10 mmol / L formic acid Second solution = methanol solution containing 10 mmol / L ammonium formate and 10 mmol / L formic acid Flow rate: 0.4mL / min Injection volume of sample B: 1 μL Detector: MS (ESI positive) Measurement mode: SCAN (mass measurement range: m / z = 100 to 1000)
[0104] (2) Analysis of organic shrinkage inhibitors (2-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials The crushed sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide to extract the organic shrink-preventing agent. Next, the first organic shrink-preventing agent and the second organic shrink-preventing agent are separated from the extract as necessary. For each of the separated products containing each organic shrink-preventing agent, insoluble components are removed by filtration, and the resulting solution is desalted, concentrated, and dried. Desalting is performed using a desalting column, or by passing the solution through an ion exchange membrane, or by placing the solution in a dialysis tube and immersing it in distilled water. This is dried to obtain a powder sample of the organic shrink-preventing agent (hereinafter referred to as sample C).
[0105] The type of organic shrinkage inhibitor is identified by combining information obtained from the following: an infrared spectrum measured using sample C of the organic shrinkage inhibitor obtained in this manner; an ultraviolet-visible absorption spectrum measured using an ultraviolet-visible spectrometer after diluting sample C with distilled water or the like; an NMR spectrum of a solution obtained by dissolving sample C in a specified solvent such as heavy water; or information obtained from pyrolysis GC / MS, which can provide information on the individual compounds that make up the substance.
[0106] The first and second organic shrink-preventing agents are separated from the extract as follows. First, the extract is measured by infrared spectroscopy, NMR, and / or GC / MS to determine whether it contains multiple organic shrink-preventing agents. Next, the extract is analyzed by GPC to measure the molecular weight distribution. If the multiple organic shrink-preventing agents can be separated by molecular weight, the organic shrink-preventing agents are separated by column chromatography based on the difference in molecular weight. If separation based on the difference in molecular weight is difficult, one of the organic shrink-preventing agents is separated by precipitation separation using the difference in solubility that differs depending on the type and / or amount of functional groups that the organic shrink-preventing agents have. Specifically, the extract is dissolved in an aqueous NaOH solution, and an aqueous sulfuric acid solution is dropped into the mixture to adjust the pH of the mixture, thereby flocculating and separating one of the organic shrink-preventing agents. The separated matter is dissolved again in an aqueous NaOH solution, and the insoluble components are removed by filtration as described above. The remaining solution after separating one of the organic shrink-preventing agents is concentrated. The resulting concentrate contains the other organic shrinkage inhibitor, and the insoluble components are removed from the concentrate by filtration as described above.
[0107] (2-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (2-1), a solution is obtained by removing insoluble components from each of the separated products containing the organic shrinkage inhibitor by filtration. The ultraviolet-visible absorption spectrum of each of the obtained solutions is measured. The content of each organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.
[0108] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, and NMR spectrum, and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.
[0109] (2-3) Sulfur content in organic shrinkage inhibitors As in (2-1) above, after obtaining sample C of the organic shrink-proofing agent, the sulfur element in 0.1 g of the organic shrink-proofing agent is converted to sulfuric acid by the oxygen combustion flask method. At this time, by burning sample C in a flask containing an adsorption solution, an eluate in which sulfate ions are dissolved in the adsorption solution is obtained. Next, the sulfur element content (c1) in 0.1 g of the organic shrink-proofing agent is obtained by titrating the eluate with barium perchlorate using thorin as an indicator. Next, c1 is multiplied by 10 to calculate the sulfur element content (μmol / g) in the organic shrink-proofing agent per 1 g.
[0110] (2-4) Mw measurement of organic shrinkage regulators As in (2-1) above, after obtaining sample C of the organic shrink-preventing agent, the GPC measurement of the organic shrink-preventing agent is carried out using the following apparatus under the following conditions. Separately, a calibration curve (calibration curve) is created from a plot of the Mw of the standard substance versus elution time. Based on this calibration curve and the GPC measurement results of the organic shrink-preventing agent, the Mw of the organic shrink-preventing agent is calculated.
[0111] GPC equipment: Build-up GPC system SD-8022 / DP-8020 / AS-8020 / CO-8020 / UV-8020 (Tosoh Corporation) Column: TSKgel G4000SWXL, G2000SWXL (7.8 mm I.D. x 30 cm) (Tosoh Corporation) Detector: UV detector, λ=210nm Eluent: A mixture of 1 mol / L NaCl aqueous solution: acetonitrile (volume ratio = 7:3) Flow rate: 1mL / min. Concentration: 10mg / mL Injection volume: 10μL Standard substance: Sodium polystyrene sulfonate (Mw=275,000, 35,000, 12,500, 7,500, 5,200, 1,680)
[0112] (3) Analysis of carbonaceous materials (3-1) Separation and quantification of carbonaceous materials The crushed sample A is used. 30 mL of nitric acid solution with a concentration of 60% by mass is added per 5 g of sample A, and heated at 70°C ± 5°C. Furthermore, 10 g of disodium ethylenediaminetetraacetate, 30 mL of ammonia water with a concentration of 28% by mass, and 100 mL of water are added per 5 g of sample A, and heating is continued to dissolve the soluble matter. The sample thus pretreated is collected by filtration. The collected sample is passed through a sieve with 500 μm openings to remove large components such as reinforcing materials, and the components that pass through the sieve are collected as carbonaceous materials.
[0113] The content of the carbonaceous material in the negative electrode material is determined by measuring the mass of the carbonaceous materials separated by the above procedure and calculating the ratio (mass %) of the total mass of the pulverized sample.
[0114] (3-2) BET specific surface area of carbonaceous materials The BET specific surface area of the carbonaceous material is determined by the gas adsorption method using the carbonaceous material separated by the above procedure (3-1) using the BET equation. The carbonaceous material is pretreated by heating at 150°C for 1 hour in a nitrogen flow to remove moisture. The BET specific surface area of the pretreated carbonaceous material is determined using the following apparatus under the following conditions. Measurement equipment: Micromeritics TriStar3000 Adsorption gas: Nitrogen gas with a purity of 99.99% or higher Adsorption temperature: liquid nitrogen boiling point (77K) Calculation method for BET specific surface area: Complies with 7.2 of JIS Z 8830:2013
[0115] (4) Determination of barium sulfate Add 50 ml of 20% by mass nitric acid to 10 g of crushed sample A, heat for about 20 minutes, and dissolve the lead components as lead ions. Filter the resulting solution to separate out solids such as carbonaceous materials and barium sulfate.
[0116] The obtained solid content is dispersed in water to obtain a dispersion, and then components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) are removed from the dispersion using a sieve. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The filtered sample is a mixed sample of the carbonaceous material and barium sulfate. The mass of the membrane filter is subtracted from the total mass of the dried mixed sample (hereinafter referred to as sample D) and the membrane filter to obtain the mass of sample D (M m ) is measured. Sample D is then placed in a crucible together with the membrane filter and incinerated at 1300°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to obtain the mass of barium sulfate (M B ) is required.
[0117] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared, for example, by adding water and sulfuric acid (or an aqueous sulfuric acid solution) to lead powder, a first surfactant, and, if necessary, at least one selected from the group consisting of an organic shrinkage inhibitor, a carbonaceous material, and other additives, and kneading the mixture. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.
[0118] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.
[0119] (Positive plate) The positive electrode plate of the lead-acid battery can be classified into a paste type, a clad type, and the like. Either a paste type or a clad type positive electrode plate may be used. The paste type positive electrode plate includes a positive electrode current collector and a positive electrode material. The configuration of the clad type positive electrode plate is as described above.
[0120] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.
[0121] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, the edge part, or the frame part of the positive electrode current collector.
[0122] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.
[0123] Unformed paste-type positive plates are obtained by filling a positive current collector with a positive paste, aging it, and drying it. The positive paste is prepared by kneading lead powder, additives, water, and sulfuric acid. Unformed clad-type positive plates are formed by filling a porous tube into which a core metal connected by a current collector is inserted with lead powder or lead powder in a slurry form, and connecting multiple tubes with a linking wire. Then, these unformed positive plates are formed to obtain positive plates.
[0124] The formation can be carried out by immersing an electrode plate group including unformed positive plates in an electrolyte solution containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group in this state. However, the formation may also be carried out before assembling the lead-acid battery or the electrode plate group.
[0125] (Separator) A separator may be disposed between the negative electrode plate and the positive electrode plate, and may be made of at least one material selected from a nonwoven fabric and a microporous membrane.
[0126] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc. can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers (for example, acid-resistant inorganic powder, polymers as binders), etc.
[0127] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and a microporous membrane mainly composed of a polymer component is preferred. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.
[0128] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.
[0129] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since the upper portions of the positive and negative plates usually have lugs, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface side of the separator (that is, a double separator is interposed between the adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.
[0130] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, which may be gelled as necessary. The electrolyte may contain the first surfactant.
[0131] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0132] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.
[0133] The specific gravity of the electrolyte at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.
[0134] (others) The lead-acid battery can be obtained by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared prior to assembling the plate group. The manufacturing method of the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, as necessary, after the step of housing the plate group and the electrolyte in the cell chamber.
[0135] Each plate in the plate group may be one or more. When the plate group includes two or more negative plates, if at least one negative plate satisfies the condition that the negative electrode material contains the first surfactant in the above content, the effect of suppressing the decrease in charge acceptance of this negative plate is obtained, and the effect of reducing the overcharged amount of electricity is obtained according to the number of such negative plates. From the viewpoint of further suppressing the decrease in charge acceptance and ensuring a high effect of reducing the overcharged amount of electricity, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of negative plates included in the plate group are negative plates that satisfy the above condition. The ratio of the negative plates that satisfy the above condition among the negative plates included in the plate group is 100% or less. All of the negative plates included in the plate group may satisfy the above condition.
[0136] When the lead-acid battery has two or more cells, it is sufficient that the plate groups of at least some of the cells have negative plates that satisfy the above conditions. From the viewpoint of further suppressing the decrease in charge acceptance and ensuring a high effect of reducing the overcharged amount of electricity, it is preferable that 50% or more (more preferably 80% or more or 90% or more) of the number of cells included in the lead-acid battery have plate groups including negative plates that satisfy the above conditions. The ratio of cells included in the lead-acid battery that have plate groups including negative plates that satisfy the above conditions is 100% or less. It is preferable that all of the plate groups included in the lead-acid battery have negative plates that satisfy the above conditions.
[0137] FIG. 1 shows an external appearance of an example of a lead-acid battery according to one embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0138] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0139] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.
[0140] The lid 15 of the lead-acid battery has a single structure (single lid), but is not limited to the illustrated example. The lid 15 may have a double structure including, for example, an inner lid and an outer lid (or a top lid). The lid having a double structure may have a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.
[0141] In this specification, the overcharge electricity quantity and the charge acceptance are evaluated according to the following procedures: The test battery used for the evaluation has a rated voltage of 2 V and a rated 5-hour rate capacity of 32 Ah.
[0142] (2) Evaluation (a) Overcharged electricity Using the above test battery in a fully charged state, the overcharged quantity of electricity is evaluated according to the following procedure. Specifically, the fully charged test battery is charged at a constant voltage of 2.4V / cell for 168 hours in a water bath at a temperature of 60±3°C. The charge current (A) during this constant voltage charge is multiplied by the charge time (h) to obtain the integrated value (Ah) of the overcharged quantity of electricity. The overcharged quantity of electricity is evaluated based on this integrated value.
[0143] (b) Charge acceptance Using a fully charged test battery, measure the amount of electricity at 10 seconds. Specifically, discharge the test battery at 6.4A for 30 minutes and leave it for 16 hours. After that, set the upper limit of the current to 200A and 2.42V / cell to measure the amount of electricity at 10 seconds. Determine The battery is charged at a voltage and the accumulated quantity of electricity for 10 seconds (the quantity of electricity at the 10th second) is measured. Both operations are carried out in a water tank at 25°C ± 2°C. The accumulated quantity of electricity for 10 seconds is used as an index for evaluating the charge acceptance.
[0144] A lead-acid battery according to one aspect of the present invention will be described below.
[0145] (1) A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate comprises a negative electrode material, The negative electrode material includes a cationic surfactant (first surfactant) having one or more hydrophobic groups and hydrophilic groups, At least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms (first hydrophobic group), A lead-acid battery, wherein the content of the cationic surfactant (first surfactant) in the negative electrode material is 10 ppm or more by mass.
[0146] (2) In the above (1), the number of the hydrophobic groups in the first surfactant may be one or more, two or more, or three or more.
[0147] (3) The lead acid battery according to claim 1 or 2, wherein in the above (1) or (2), the first surfactant includes a quaternary ammonium salt.
[0148] (4) In the above (3), the number of the first hydrophobic groups contained in one molecule of the quaternary ammonium salt may be 4 or less, 3 or less, or 2 or less.
[0149] (5) In any one of the above (1) to (4), the first hydrophobic group may have 10 or more, 14 or more, 16 or more, or 18 or more carbon atoms.
[0150] (6) In any one of the above (1) to (5), the first hydrophobic group may have 30 or less, 26 or less, 24 or less, or 22 or less carbon atoms.
[0151] (7) In any one of the above (1) to (6), at least one of the hydrophobic groups may be a long-chain aliphatic hydrocarbon group having 16 or more carbon atoms as the first hydrophobic group.
[0152] (8) In any one of the above (1) to (7), the first surfactant may have a second hydrophobic group other than the first hydrophobic group.
[0153] (9) In any one of the above (1) to (8), the content of the first surfactant in the negative electrode material may be, by mass, 10 ppm or more, 50 ppm or more, 100 ppm or more, 150 ppm or more, 250 ppm or more, or 300 ppm or more.
[0154] (10) In any one of the above (1) to (9), the content of the first surfactant in the negative electrode material may be, by mass, 1000 ppm or less, 700 ppm or less, 600 ppm or less, 500 ppm or less, 400 ppm or less, or 300 ppm or less.
[0155] (11) In any one of the above (1) to (10), the negative electrode material may contain an organic shrinkage preventer.
[0156] (12) In the above (11), the negative electrode material may contain a lignin compound as the organic shrinkage preventer.
[0157] (13) In the above (11) or (12), the negative electrode material may contain a condensate of a bisarene compound as the organic shrinkage preventer.
[0158] (14) In any one of the above (11) to (13), the content of the organic shrink-preventing agent in the negative electrode material may be 0.005% by mass or more, or 0.01% by mass or more.
[0159] (15) In any one of the above (11) to (14), the content of the organic shrinkage preventer in the negative electrode material may be 1.0 mass % or less, 0.5 mass % or less, 0.3 mass % or less, or 0.25 mass % or less.
[0160] (16) In any one of the above (1) to (15), the negative electrode material may contain a carbonaceous material.
[0161] (17) In the above (16), the specific surface area of the carbonaceous material is 0.5 (m 2 ·g -1 ) or more, 1(m 2 ·g -1 ) or more, 20(m 2 ·g -1 ) or more, 300(m 2 ·g -1 ) or more than 400(m 2 ·g -1 ) or more.
[0162] (18) In the above (16) or (17), the specific surface area of the carbonaceous material is 1500 (m 2 ·g -1 ) or less, 1000(m 2 ·g -1 ) or less, 800(m2 ·g -1 ) or less, 200(m 2 ·g -1 ) or less, or 150(m 2 ·g -1 ) or less.
[0163] (19) In any one of the above (16) to (18), the content of the carbonaceous material in the negative electrode material may be 0.05 mass % or more, or 0.10 mass % or more.
[0164] (20) In any one of the above (16) to (19), the content of the carbonaceous material in the negative electrode material may be 5 mass % or less, or 3 mass % or less.
[0165] (21) In any one of the above (1) to (20), the negative electrode material may contain barium sulfate.
[0166] (22) In the above (21), the content of the barium sulfate in the negative electrode material may be 0.05% by mass or more, or 0.10% by mass or more.
[0167] (23) In the above (21) or (22), the content of the barium sulfate in the negative electrode material may be 3 mass % or less, or 2 mass % or less.
[0168] (24) In any one of the above (1) to (23), the specific gravity of the electrolyte in the lead-acid battery in a fully charged state at 20° C. may be 1.20 or more, or 1.25 or more.
[0169] (25) In any one of the above (1) to (24), the specific gravity of the electrolyte in the lead-acid battery in a fully charged state at 20° C. may be 1.35 or less, or 1.32 or less.
[0170] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0171] Lead-acid batteries E1 to E17 and C1 to C10 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate The raw material lead powder, barium sulfate, carbon black as a carbonaceous material, a surfactant shown in the table, and an organic shrinkage inhibitor shown in the table are mixed with an appropriate amount of sulfuric acid aqueous solution to obtain a negative electrode paste. At this time, the components are mixed so that the content of the first surfactant in the negative electrode material, which is obtained by the procedure described above, is the value shown in the table, the content of the organic shrinkage inhibitor is 0.1 mass%, the content of the barium sulfate is 0.4 mass%, and the content of the carbon black is 0.2 mass%. The negative electrode paste is filled into the mesh part of an expanded lattice made of a Pb-Ca-Sn alloy, and aged and dried to obtain an unformed negative electrode plate.
[0172] As the organic shrink inhibitors shown in the table, the following components are used. (e1) Lignin: Sodium lignosulfonate (sulfur element content 600 μmol / g, Mw 5500) (e2) Bisphenol condensate: Condensation product of a bisphenol compound having a sulfonic acid group introduced therein with formaldehyde (sulfur element content: 5000 μmol / g, Mw: 9600)
[0173] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste, which is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged and dried to obtain an unformed positive electrode plate.
[0174] (c) Preparation of test battery The test battery has a rated voltage of 2V and a rated 5-hour rate capacity of 32Ah. The plate assembly of the test battery consists of seven positive plates and seven negative plates. The negative plates are housed in a pouch-shaped separator made of a microporous polyethylene film and are stacked alternately with the positive plates to form a plate assembly. The plate assembly is housed in a polypropylene container together with an electrolyte (aqueous sulfuric acid solution) and chemically treated in the container to create a liquid-type lead-acid battery. The specific gravity of the electrolyte in a fully charged lead-acid battery at 20°C is 1.28.
[0175] (2) Evaluation (a) Overcharged electricity The integrated value of the overcharged quantity of electricity of the lead-acid batteries is obtained by the above-mentioned procedure. The overcharged quantity of electricity of each lead-acid battery is evaluated as a ratio when the integrated value of the overcharged quantity of electricity of the lead-acid battery C1 is set to 100.
[0176] (b) Charge acceptance The lead-acid batteries are measured for 10 seconds by the above-mentioned procedure. The charge acceptance of each lead-acid battery is evaluated based on the ratio of the accumulated amount of electricity of the lead-acid battery C1 to 100.
[0177] The results are shown in Tables 1 to 3. The tables also show the ratio (A) / (B) of the evaluation result of charge acceptance (A) to the evaluation result of overcharge quantity of electricity (B). When the ratio (A) / (B) is 1 or less, it indicates an excellent balance between high charge acceptance and low overcharge quantity of electricity. E1 to E17 are examples, and C1 to C10 are comparative examples. Table 3 also shows the specific surface area of the carbonaceous material contained in the negative electrode material.
[0178] [Table 1]
[0179] As shown in Table 1, when the negative electrode material contains tetramethylammonium chloride or tetrapropylammonium chloride, which is a second surfactant other than the first surfactant, the charge acceptance is improved compared to when no surfactant is contained, but the overcharge charge cannot be reduced (compare C1 with C2 to C7). However, when the negative electrode material contains the first surfactant, the overcharge charge can be reduced while maintaining a relatively high charge acceptance (E1 to E12).
[0180] From the viewpoint of further enhancing the effect of reducing the overcharge quantity of electricity, it is preferable that the negative electrode material contains a quaternary ammonium salt type first surfactant. From the same viewpoint, it is preferable that the negative electrode material contains at least a first surfactant having a long-chain aliphatic hydrocarbon group having 14 or more carbon atoms or 16 or more carbon atoms as the first hydrophobic group. It is also preferable that the negative electrode material contains a first surfactant having a long-chain aliphatic hydrocarbon group having 18 or more carbon atoms as the first hydrophobic group, or a first surfactant having two or more first hydrophobic groups.
[0181] [Table 2]
[0182] As shown in Table 2, even when a lignin compound is used as the organic shrinkage inhibitor, high charge acceptance can be ensured while suppressing the amount of overcharge electricity to a low level. When a condensate of a bisarene compound is used as the organic shrinkage inhibitor, higher charge acceptance can be ensured compared to when a lignin compound is used.
[0183] [Table 3]
[0184] As shown in Table 3, when the negative electrode material does not contain the first surfactant, as the specific surface area of the carbonaceous material increases, the charge acceptance increases, but the overcharge quantity of electricity tends to increase. When the negative electrode material contains the first surfactant, even if the specific surface area of the carbonaceous material increases, the overcharge quantity of electricity can be reduced while maintaining a relatively high charge acceptance. [Industrial Applicability]
[0185] The lead-acid battery according to one aspect of the present invention is suitable for use in an idle-stop vehicle as an IS lead-acid battery that is charged and discharged under PSOC conditions. The lead-acid battery can also be suitably used as a starting power source for vehicles (such as automobiles and motorcycles) and industrial power storage devices (such as power sources for electric vehicles (such as forklifts)). Note that these are merely examples, and the uses of the lead-acid battery are not limited to these. [Explanation of symbols]
[0186] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug
Claims
1. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate comprises a negative electrode material, The negative electrode material includes a cationic surfactant having one or more hydrophobic groups and hydrophilic groups; At least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms, A lead-acid battery, wherein the content of the cationic surfactant in the negative electrode material is 10 ppm or more and 600 ppm or less by mass.
2. The lead-acid battery according to claim 1 , wherein the content of the cationic surfactant in the negative electrode material is 50 ppm or more by mass.
3. A lead-acid battery, The lead-acid battery includes at least one cell including a plate group and an electrolyte; the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate, The negative electrode plate comprises a negative electrode material, The negative electrode material includes a cationic surfactant having one or more hydrophobic groups and hydrophilic groups; At least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 8 or more carbon atoms, The content of the cationic surfactant in the negative electrode material is 50 ppm or more by mass.
4. The lead acid battery according to any one of claims 1 to 3, wherein at least one of the hydrophobic groups is a long-chain aliphatic hydrocarbon group having 16 or more carbon atoms.
5. The lead acid battery according to any one of claims 1 to 4, wherein the cationic surfactant includes a quaternary ammonium salt.
6. The lead acid battery according to any one of claims 1 to 5, wherein the long-chain aliphatic hydrocarbon group has 26 or less carbon atoms.
7. The lead acid battery according to any one of claims 1 to 6, wherein the negative electrode material comprises a condensate of a bisarene compound.
Citation Information
Patent Citations
Electrolytic solution for lead storage battery, anode for lead storage battery, lead storage battery equipped with electrolytic solution and / or anode, and additive for lead acid battery
JP2008152973A
Negative electrode plate for lead acid storage battery, and lead acid storage battery using the negative electrode plate
JP2012043594A
Electrochemical cell
US20020102467A1
Lead storage battery
WO2013058058A1